Berberine Influences Blood Glucose via Modulating the Gut Microbiome in Grass Carp - Pan, Houjun; Li, Zhifei; Xie, Jun; Liu, Duan; Wang, Hongjuan; Yu, Deguang; Zhang, Qing; Hu, Zhiyi; Shi, Cunbin (Frontiers in Microbiology, 2019)
Berberine (BBR), an isoquinoline alkaloid, is a major pharmacological component of the Chinese herb Coptis chinensis, which has been listed in the Chinese Fisheries Pharmacopoeia as a common drug for the control of bacterial fish diseases. However BBR is poorly absorbed into the systemic circulation but is significantly accumulated in the intestine. It is difficult to explain the mechanism of clinical effects of BBR based on systemic genes and pathways; it has been proved that the function of BBR in mammals is associated with the host metabolic phenotypes mediated by the structural modulation of gut microbiota. The mechanism of pharmacological effects of BBR in fish remains unclear. Here, we fed grass carp (Ctenopharyngodon idellus) a diet supplemented with BBR at a dose of 30 mg/Kg body weight daily and compared them with grass carp fed a regular fish feed diet. Biochemical analysis revealed that fish fed BBR had significantly reduced serum glucose, total cholesterol (TC), and triglyceride (TG) levels, and increased TC (p < 0.05) and TG (p < 0.01) levels in the liver. Deep amplicon sequencing of the V4 region of 16S rRNA genes of the gut microbiota revealed: (i) the composition of gut microbiota after BBR feeding was more diverse than that in the control group; (ii)before fish were fed BBR, the enriched operational taxonomic units (OTUs ) mainly belonged to Firmicutes while most enriched OTUs came from Proteobacteria, Planctomycetes, Bacteroidetes, and Firmicutes during BBR feeding and after BBR feeding stopped; (iii) the ratio of Firmicutes to Bacteroidetes was significantly decreased in fish fed BBR. Spearman’s rank correlation showed that 32 berberine-OTUs were significantly negative correlated with glucose (p<0.05). It indicates that BBR may affect the levels of serum glucose by the structural modulation of gut microbiota. Our results provide insight into the effect of BBR on fish metabolism and gut microbiomes, which would be beneficial for the fish Welfare.